Functional roles of the A335 and G338 residues of the proton-coupled folate transporter (PCFT-SLC46A1) mutated in hereditary folate malabsorption - Shin, Daniel Sanghoon (American Physiological Society, 2012)
The proton-coupled folate transporter (PCFT-SLC46A1) mediates intestinal folate absorption and folate transport across the choroid plexus, processes defective in hereditary folate malabsorption (HFM). This paper characterizes the functional defect, and the roles of two mutated PCFT residues, associated with HFM (G338R and A335D). The A335D-PCFT and other mutations at this residue result in an unstable protein; when expression of a mutant protein was preserved, function was always retained. The G338R and other charged mutants resulted in an unstable protein; substitutions with small neutral and polar amino acids preserved protein but with impaired function. Pemetrexed and methotrexate (MTX) influx kinetics mediated by the G338C mutant PCFT revealed marked (15- to 20-fold) decreases in K(t) and V(max) compared with wild-type PCFT. In contrast, there was only a small (∼2-fold) decrease in the MTX influx K(i) and an increase (∼3-fold) in the pemetrexed influx K(i) for the G338C-PCFT mutant. Neither a decrease in pH to 4.5, nor an increase to 7.4, restored function of the G338C mutant relative to wild-type PCFT excluding a role for this residue in proton binding or proton coupling. Homology modeling localized the A335 and G338 residues embedded in the 9th transmembrane, consistent with the inaccessibility of the A335C and G338C proteins to MTS reagents. Hence, the loss of intrinsic G338C-PCFT function was due solely to impaired oscillation of the carrier between its conformational states. The data illustrate how alterations in carrier cycling can impact influx K(t) without comparable alterations in substrate binding to the carrier.